The nitrogen/phosphorus and the succession of phytoplankton in two lakes located in the alluvial prairie of main river in Germany (2006)
ABSTRACT : Variation in seasonal nitrogen/phosphorus ratio and phytoplankton community succession were compared between March and November 1997 in a lake directly connected to the Main River and in another lake without direct connection. Results showed a massive growth of Cyanophyta during summer in association with low N/P ratios (10-5:1), whereas Crysophyta and Chlorophyta abundance was accompanied by high N/P ratios (50-20:1). Evidences suggest that composition and structure of the phytoplankton community are related to phosphorus and nitrogen availability, and also contributes to the appearance of new phytoplanktonic species. However phytoplanktonic community succession were more correlated with the dominance degree of some species.